Aggravation et modulation contextuelle de symptômes obsessionnels-compulsifs lors de tentatives de réinsertion communautaire chez un homme présentant un trouble psychotique et un trouble de stress post-traumatique complexe : étude de cas. - Hudon, Alexandre; Mongeon, Sophie; Borduas Pagé, Stéphanie; Chainey, Fanie (Sante Mentale au Quebec)
This case report describes the clinical course of an adult man followed in forensic and community psychiatry, presenting a complex history of a psychotic disorder, developmental trauma, severe polysubstance use, and prolonged social marginalization. The originality of this case lies in the progressive emergence of atypical obsessive-compulsive phenomena during phases of structured psychosocial reintegration. These phenomena intensify in contexts of multiple relational and institutional demands and attenuate when the patient withdraws from certain commitments or imposed frameworks. Predominant symptoms include persistent intrusive ruminations, ritualized somatic self-soothing behaviors, and repetitive actions that are poorly modifiable through reasoning. The differential diagnosis, therapeutic interventions, and clinical evolution are discussed in light of contemporary models of obsessive-compulsive disorders, complex post-traumatic stress disorder, and reintegration trajectories among justice-involved patients with psychotic disorders. This case highlights the importance of considering the psychosocial environment as a dynamic factor that may exacerbate or mitigate obsessive-compulsive symptoms, independently of apparent psychotic stability.